Internal Communication Analysis, Style Democratic Leadership and Work Culture on Employee Performance through Motivation as Mediation (Case Study at SDN Kramat 08) - Andika Karunia Saputro; Gatot Prabantoro (MJK PUBLISHER, 2024)
Human resources (HR) are one of the most important factors that cannot be separated from an organization, both companies and institutions. In addition, HR is also a factor that influences the development of a company. So, it can be said that a company can develop very rapidly if it has many competent HR in its field, conversely if the HR working in a company is not qualified, the development of the company will also be hampered. This study aims to identify how internal communication, democratic leadership style, work culture, motivation and employee performance at SDN Kramat 08. The research method used is descriptive quantitative, by making the entire population as respondents of the study as many as 25 employees. The results of the study showed that the results of the respondents were quite good by answering